THE USAGE OF METHODS OF PSYCHODIAGNOSTIC OBSERVATION AND INTERVIEW IN THE RESEARCH OF SOCIAL INSTALLATIONS ROLE WITHIN THE PROCESS OF EATING BEHAVIOR DEFORMATIONS - SHAHINYAN, HASMIK (Main Issues Of Pedagogy And Psychology, 2015)
The article refers to the discussion of the usage of methods of psychodiagnostic observation and interview within the process of research of social installations causing eating behavior deformations in the adolecent girls. The article also refers to the analisys of data and regulations maintained in the process of research.